Acylruthenium Complexes from Reactions of RuCl2(PPh3)3 with Terminal Alkynes. Issue 6 (12th February 2020) - Sha, Yuzhuo; Bai, Wei; Zhou, Yan; Jiang, Jingyang; Ju, Xianchun
Abstract: Reactions of 1‐phenylethyne HC≡C−Ph and 1‐octyne HC≡C‐(CH2 )5 CH3 with RuCl2 (PPh3 )3 (1 ) were carried out in the presence of concentrated HCl aqueous solution, and new acyl complexes Ru(=C=CHPh)(‐C(=O)CH2 Ph)Cl(PPh3 )2 (2 ) and Ru(‐C(=O)(CH2 )6 CH3 )Cl(CO)(PPh3 )2 (3 ) are isolated. Further decarbonylation produces Ru(‐C(CH2 Ph)=CHPh)Cl(CO)(PPh3 )2 (4 ) and RuHCl(CO)2 (PPh3 )2 (5 ), respectively. These are the first examples of stoichiometric anti‐Markovnikov hydration of terminal alkynes involving complexes without polydentate ligands. Abstract : Only ruthenium complexes with a half‐sandwich structure or polydentate ligands are reported to assist anti‐Markovnikov hydration of terminal alkynes. This work describes reactions of RuCl2 (PPh3 )3 with 1‐phenylethyne and 1‐octyne, involving stoichiometric anti‐Markovnikov hydration and decarbonylation.